2004
DOI: 10.1063/1.1695637
|View full text |Cite
|
Sign up to set email alerts
|

Efficient electron spin detection with positively charged quantum dots

Abstract: We report the application of time-and polarization-resolved photoluminescence up-conversion spectroscopy to the study of spin capture and energy relaxation in positively and negatively charged, as well as neutral, InAs self-assembled quantum dots. When compared to the neutral dots, we find that carrier capture and relaxation to the ground state is much faster in the highly charged dots, suggesting that electron-hole scattering dominates this process. The long spin lifetime, short capture time, and high radiati… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
21
1

Year Published

2005
2005
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 22 publications
3
21
1
Order By: Relevance
“…This assumption is based on a simple observation that a charged QD attracts particles of the opposite charge and repels like-charged ones and also on the experimental results of Ref. 26. An evident consequence is that the opposite-charge carrier lives for some time in the QD before the coming of the like-charge one; during this time interval, the QD contains not a tetron, but a trion.…”
Section: A Qualitative Explanation Of the Experimental Resultsmentioning
confidence: 99%
“…This assumption is based on a simple observation that a charged QD attracts particles of the opposite charge and repels like-charged ones and also on the experimental results of Ref. 26. An evident consequence is that the opposite-charge carrier lives for some time in the QD before the coming of the like-charge one; during this time interval, the QD contains not a tetron, but a trion.…”
Section: A Qualitative Explanation Of the Experimental Resultsmentioning
confidence: 99%
“…The rate for the injection and the subsequent relaxation of electrons into the conduction band ground state in the dot α is denoted by W eα . It has been demonstrated that this entire process is spin conserving and occurs much faster than the optical recombination 5,6 , which is described by the rates W pα . Typically, W pα ∼ 1 (ns)…”
Section: A Electron Injection and Photon Emissionmentioning
confidence: 99%
“…Spin light-emitting diodes (spin-LEDs), 1,2,3,4,5,6,7,8 in which electron recombination is accompanied by the emission of a photon with well-defined circular polarization, provide an efficient interface between electron spins and photons. The operation of such devices at the single-photon level would allow one to convert the quantum state of an electron encoded in its spin state into that of a photon with a wide range of possible applications.…”
Section: Introductionmentioning
confidence: 99%
“…The spin-dependent transport properties are of particular interest for its possible applications, e.g., the QD spin valves (Konig & Martinek, 2003), the quantum logic gates using coupled QDs, as well as the spin-dependent transport in single-electron devices (Seneor et al, 2007), etc.. In such systems, the electron-electron exchange potential and the electron spin states have been utilized and manipulated (Burkard et al, 2000;Gundogdu et al, 2004;Sarma et al, 2001;Wolf et al, 2001). A thorough quantitative understanding of spin-dependent transport properties due to electron-electron interaction is therefore important for a successful construction of these devices.…”
Section: Introductionmentioning
confidence: 99%